2012
DOI: 10.1021/am201796k
|View full text |Cite
|
Sign up to set email alerts
|

Strong Adhesion and Friction Coupling in Hierarchical Carbon Nanotube Arrays for Dry Adhesive Applications

Abstract: The adhesion and friction coupling of hierarchical carbon nanotube arrays was investigated with a hierarchical multiscale modeling approach. At device level, vertically aligned carbon nanotube (VA-CNT) arrays with laterally distributed segments on top were analyzed via finite element methods to determine the macroscopic adhesion and friction force coupling. At the nanoscale, molecular dynamics simulation was performed to explore the origin of the adhesion enhancement due to the existence of the laterally distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 56 publications
0
37
0
4
Order By: Relevance
“…The presence of pull-off forces found by other authors can be explained with different testing methods and VACNT arrangements [19,20,22,38]. Testing of adhesion of VACNTs by pressing with a plate led to an anisotropic alignment of the tips of the 200-500 µm long CNTs in parallel to the test surface [20].…”
Section: Absence Of Pull-off Forcesmentioning
confidence: 80%
See 1 more Smart Citation
“…The presence of pull-off forces found by other authors can be explained with different testing methods and VACNT arrangements [19,20,22,38]. Testing of adhesion of VACNTs by pressing with a plate led to an anisotropic alignment of the tips of the 200-500 µm long CNTs in parallel to the test surface [20].…”
Section: Absence Of Pull-off Forcesmentioning
confidence: 80%
“…This kind of deformation led to attachment of the CNTs to the test substrate by their sides, and that is why normal pull-off forces, presumably caused by shear adhesion between the single CNTs and the substrate, increased with preload. The latter was later predicted by Finite Element Analysis [38]. Chen et al [22] reported significant pull-off forces from micro-patterned 170-230 µm high VACNT pillar-like arrays, and an influence of pillar aspect ratio and spacing on both EEM and adhesion strength.…”
Section: Absence Of Pull-off Forcesmentioning
confidence: 93%
“… (C) Schematic diagram of carbon nanotube modifications with polydopamine ( Li et al., 2019 ). (D) Schematics of vertical aligned CNT arrays with laterally distributed CNT segments adhering on a target surface; FEA model for simulating the macroscopic adhesive behaviors of vertical aligned CNT arrays and a snapshot of a lateral CNT being peeled from substrate in molecular dynamics ( Hu et al., 2012 ). (E) Schematic diagram of the self-healing principle of a mussel thread ( Xu et al., 2019 ).…”
Section: Process Design and Function Classificationmentioning
confidence: 99%
“… (D) Schematics of vertical aligned CNT arrays with laterally distributed CNT segments adhering on a target surface; FEA model for simulating the macroscopic adhesive behaviors of vertical aligned CNT arrays and a snapshot of a lateral CNT being peeled from substrate in molecular dynamics ( Hu et al., 2012 ). …”
Section: Process Design and Function Classificationmentioning
confidence: 99%
See 1 more Smart Citation